Peningkatan Citra Untuk Memperjelas Foto Brain Ct Scan - Priyono Yulianto (Universitas Muhammadiyah Yogyakarta, 2008)
The CT scan brain photo represent medical image result from Computer Tomographi (CT) Scanner process, normally obtained on photographic negative transparencies. The brain images were acquired from a CT scan photo presenting colour gradation in to gray level, that is : white colour, gray and black colour. In general have histogram which tend to reside in around dark in to gray level, so that its image less clear if seen with naked eye. and can be told exploiting of digital image enhancement not yet is optimal. The research was to show that digital image enhancement used to clarify photograph CT scan brain image. Data collecting done with procedure chosen normal diagnostic CT-scan brain photo and which have indication damage of brain effect of ischemic stroke. The CT scan brain photo so that can be processed must be done scanning beforehand for the image digitization is quantization. The image enhancement techniques can be processed is : histogram equalization transform, contrast stretching transform, histogram classify, region of interst to enhancement and edge detection. Histogram equalization (Histeq) transform, contrast stretching transform, histogram classify, region of interst to enhancement (ROI) and edge detection transform can be used for clarify CT scan brain photo, so that can assist radiology doctor in is diagnostic of disparity or damage brain effect of ischemic stroke.